Penerapan Quality of Service Pada Jaringan Internet Menggunakan Metode Hierarchical Token Bucket - Claudi Priambodo Antodi; Agung Budi Prasetijo; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2017)
One of the problems frequently encountered by internet users is slow internet access. In particular, when there are many users share the internet bandwidth. This problem may occur as there is no bandwidth management system employed. HTB is one of the bandwidth management system available on Linux that can be installed on a network. This research focuses on the implementation of the HTB as a bandwidth management system. Based on the testing done, it is shown that after using HTB as bandwidth manager, internet access can be controlled and every client gets bandwidth as needed. The performance achieved when HTB is employed outperforms the non-HTB scenario. With HTB, the packet loss and failed transaction are reduced more than 90%.